2020
DOI: 10.1016/j.ijnurstu.2020.103590
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between independent nurse prescribing and patient group directions in the safety and appropriateness of medication provision in United Kingdom sexual health services: A mixed methods study

Abstract: A comparison between independent nurse prescribing and patient group directions in the safety and appropriateness of medication provision in United Kingdom sexual health services: a mixed methods study,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
(65 reference statements)
1
12
0
Order By: Relevance
“…Overall, 713 of 743 (96.0%) of all nurse prescriber medication decisions were considered safe, as were 927 of 939 (98.7%) of patient group directions decisions (Fisher's Exact, p = .55). For more details see Black et al (2020).…”
Section: Results/findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 713 of 743 (96.0%) of all nurse prescriber medication decisions were considered safe, as were 927 of 939 (98.7%) of patient group directions decisions (Fisher's Exact, p = .55). For more details see Black et al (2020).…”
Section: Results/findingsmentioning
confidence: 99%
“…Slightly higher error rates per consultation were recorded by nurse prescribers (1.18) than by nurses using patient group directions (1.03), but errors were predominantly judged minor and often attributed to documentation omissions. No patients were known to have been harmed from any errors identified (further details Black et al, 2020). One strength of this study is that it explored medication errors for patients who did not receive medications, that is, potential of under‐prescribing, whilst other large prescribing studies focus specifically on circumstances in which medication was provided (Avery et al, 2012; Dornan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that expanding health care worker scopes of practice to encompass prescribing and administering restricted medicines improves access to and quality of care, particularly for rural or other underserved populations (94,209,(232)(233)(234)(235)(236)(237)(238)(239)(240)(241)(242)(243)(244)(245)(246). The role of regulators includes setting the necessary competencies, accrediting training programs, monitoring compliance with standards for safe use of medicines and dealing with registrants breaching accepted practice standards (6,247).…”
Section: Regulation Of Scopes Of Practicementioning
confidence: 99%
“…The advantages of nurse pharmaceutical care are that they allow for more rapid prescription availability, more patient options for access, higher e cacy of patient service, and more e cient utilization of nurses' training and education [5]. Within the a number of European nations, psychiatric/mental health nurses have taken active roles in PC for a number of years [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Yang found that medication prescriptions by nurses and doctors were essentially identical in regard to content and frequency [18]. Furthermore, when appraising the outcomes of medication, such as the observation of adverse events, side effects, and client and family education, nurse prescribers were able to offer their patients more time and acuity than their medical counterparts [5].…”
Section: Introductionmentioning
confidence: 99%